Operative transportation planning : Solutions in consumer goods supply chains - Seiler, Thorben (Contributions to Management Science,, 2012)
Transportation management in today's consumer goods industry can be characterized by a high proportion of outsourced transportation services. Due to rising freight costs consumer goods manufacturers are seeking opportunities to increase the efficiency of their transportation network. This book presents an operational transportation planning problem typical of the consumer goods industry focusing on a network of suppliers, production facilities and warehouses. With respect to the large share of outsourcing in these networks a detailed analysis of freight costs based on contractual agreements is provided. From this analysis a number of opportunities for efficiency gains are identified and consolidated in an operative transportation planning problem that is numerically investigated. Furthermore, an overview of processes and organizational requirements in transportation management is given with special focus on the integration of existing commercial Transportation Management Systems (TMS).